2005
DOI: 10.1242/jcs.02323
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of redox signaling in mammalian cells enabled by controlled photogeneration of reactive oxygen species

Abstract: Reactive oxygen species (ROS) comprise a group of noxious byproducts of oxidative processes which participate in the induction of many common diseases. However, understanding their role in the regulation of normal physiological redox signaling is currently evolving. Detailed study of the dynamic functions of ROS within the biological milieu is difficult because of their high chemical reactivity, short lifetime, minute concentrations and cytotoxicity at high concentrations. In this study, we show that increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 64 publications
2
34
0
Order By: Relevance
“…Previously, this was attributed to the reaction between · OH and HE [32]. However, we found that SOD vastly diminished 2-OH-E + formation, suggesting that superoxide is responsible for 2-OH-E + generation in this system.…”
Section: Discussionmentioning
confidence: 49%
“…Previously, this was attributed to the reaction between · OH and HE [32]. However, we found that SOD vastly diminished 2-OH-E + formation, suggesting that superoxide is responsible for 2-OH-E + generation in this system.…”
Section: Discussionmentioning
confidence: 49%
“…Indeed, such a process has been demonstrated for both JNK1/2 (18,19) and p38␣/␤ (20,21) in some systems. However, in other studies, it was suggested that JNK1/2 (22, 23) and p38␣/␤ (24,25) are in fact localized in the nucleus of resting cells. For the latter, it was even shown that after stimulation it is exported out of the nucleus (26).…”
mentioning
confidence: 90%
“…While the mechanism for TH preservation of Akt phosphorylation is unknown, it could potentially alter the relative balance of kinase or phosphatase activity. Alternatively, TH could modulate Akt activity through the activation of heat shock/cold shock proteins or the modulation of reactive oxygen species-sensitive signaling pathways (10,35,39). The observed reduction in Akt phosphorylation in Akt1 ϩ/Ϫ mice could reflect a change in the relative stoichiometry of Akt, kinases, and phosphatases including protein phosphatase 2 in these animals.…”
Section: Discussionmentioning
confidence: 99%